2016
DOI: 10.17221/169/2015-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Potential anthelmintic effect of Capparis spinosa (Capparidaceae) as related to its polyphenolic content and antioxidant activity

Abstract: ABSTRACT:Capparis spinosa is cultivated for several proprieties and the different parts of the plant (flower buds, fruits, leaf and seeds) have been employed in drugs, foods and cosmetics. This study aimed to explore the antioxidant potential effect and to assess the anthelmintic efficacy of an aqueous extract of Capparis spinosa. In vitro antioxidant activity of aqueous extracts from the fresh leaves and flower buds of C. spinosa was measured by determining free radical-scavenging activity against DPPH and AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…However, the anthelmintic mechanism of action is unknown. It seems that flavonoids with antioxidant capacity, in particular, contribute to the indirect antiparasitic activity [34,35]. However, not only the content of flavonoids appears to play an important role in the anthelmintic activity of medicinal plants and their mixtures.…”
Section: Discussionmentioning
confidence: 99%
“…However, the anthelmintic mechanism of action is unknown. It seems that flavonoids with antioxidant capacity, in particular, contribute to the indirect antiparasitic activity [34,35]. However, not only the content of flavonoids appears to play an important role in the anthelmintic activity of medicinal plants and their mixtures.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found a promissory anthelmintic activity against eggs and adult worms of Haemonchus contortus from sheep, while they correlated these effects to the high content of phenolic compounds (i.e. flavonoids and tannins (Akkari et al, 2016). The anti-inflammatory activity of caper was also detected in animal studies, where leaf extracts were able to reduce edema in treated mice in a dose-dependent manner, as also a significant decrease in immune cells infiltration, vasodilatation and in dermis thickness (Azhary et al, 2017).…”
Section: Health Effectsmentioning
confidence: 91%
“…Cytotoxic activity of the plant was also assessed, being observed a high selectivity against human cancer cell lines, namely: breast adenocarcinoma (MCF-7), hepatocellular carcinoma (Hep-G2), and colon carcinoma (HCT-116 and HT-29) cells, suggesting their upcoming use as a promissory candidate for nutraceutical researches (Bakr & Bishbishy, 2016). Anthelmintic effects of the species were also reported as being related to its phenolic content and antioxidant activity (Akkari et al, 2016). The authors found a promissory anthelmintic activity against eggs and adult worms of Haemonchus contortus from sheep, while they correlated these effects to the high content of phenolic compounds (i.e.…”
Section: Health Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total flavonoids registered 57 mg Quercetin Equivalent (QE)/g DW in hydroethanol extract of leaves and ranged from 2.6 to 6.96 mg QE /g DW in leaves methanol extract, whereas, 13.97 mg QE/ g DW and 25 mg QE/ g DW were found in leaves and flowers aqueous extracts respectively. Roots and fruits ethyl acetate extracts had a content of flavonoids of 95.5 and 18.1 mg QE/g respectively (Bhoyar et al, 2011 ; Mahboubi and Mahboubi, 2014 ; Akkari et al, 2016 ; Mansour et al, 2016 ). According to Inocencio et al ( 2000 ), 10 g of commercial caper bud will provide 40 mg QE as aglycone in Mediterranean countries (Spain, Turkey, Morocco, Italy, Greece).…”
Section: Phytochemical Composition and Activitiesmentioning
confidence: 99%